2022
DOI: 10.1038/s41467-022-29185-9
|View full text |Cite
|
Sign up to set email alerts
|

Flexible auditory training, psychophysics, and enrichment of common marmosets with an automated, touchscreen-based system

Abstract: Devising new and more efficient protocols to analyze the phenotypes of non-human primates, as well as their complex nervous systems, is rapidly becoming of paramount importance. This is because with genome-editing techniques, recently adopted to non-human primates, new animal models for fundamental and translational research have been established. One aspect in particular, namely cognitive hearing, has been difficult to assess compared to visual cognition. To address this, we devised autonomous, standardized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 100 publications
2
23
0
Order By: Relevance
“…In this study, we adapted a visuo-acoustic automated unsupervised training protocol (AUT) we previously used to train marmoset monkeys ( Calapai et al, 2022 ). Here, 5 long-tailed macaques belonging to 2 groups underwent an AUT comprised 49 training steps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we adapted a visuo-acoustic automated unsupervised training protocol (AUT) we previously used to train marmoset monkeys ( Calapai et al, 2022 ). Here, 5 long-tailed macaques belonging to 2 groups underwent an AUT comprised 49 training steps.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it shared the structural design of the apparatus described for Rhesus macaques (Berger et al, 2018) while replacing costly hardware (Apple computers) with an open-source system (Raspberry Pi computers), allowing for more straightforward modification and expansion of the system by others. It additionally used a visuo-acoustic protocol developed for common marmosets Frontiers in Psychology 09 frontiersin.org (Calapai et al, 2022). Furthermore, our protocol relies on computer vision technology for the identification of subjects on a trial basis, which could, in principle, allow for testing subjects in natural settings.…”
Section: Visuo-acoustic Automated Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…This system would be able to accurately quantify the behavior of marmosets throughout their lives to discover behavioral changes before and after the onset of diseases, even at an extremely early stage. Recently Calapai et al reported a new touch screen based cognitive auditory analysis system that allows marmosets to perform tasks in a free moving environment in the paired home cage 44 . By incorporating such a freely operable cognitive function task device into our system, it is possible to provide a behavior analysis system that comprehensively and continuously analyzes the marmoset's natural behavior, activity, and cognitive functions without stress.…”
Section: Discussionmentioning
confidence: 99%
“…The collection of these data can be automated using radio frequency identification (RFID) tags. RFID tags are worn on a collar or implanted into the skin and have been used to monitor several laboratory primate species, such as rhesus macaques ( Macaca mulatta ) ( 17 ); common marmosets ( Callithrix jacchus ) ( 18 ); guinea baboons ( Papio papio ) ( 19 , 20 ). However, there are several reasons why this approach may be deemed unsuitable.…”
Section: Introductionmentioning
confidence: 99%